Sikap Ã¢â‚¬Å“SilenceÃ¢â‚¬Â Terhadap Niat Melakukan Whistleblowing - Dewi, Ayu Aryista; Anggara, I Wayan Gde Wahyu Purna (Fakultas Ekonomi Universitas Negeri Manado, 2024)
This study aims to examine the influence of silence, subjective norms, and personal reporting costs on whistleblowing intentions, as well as the perception of organizational support as a moderating variable. The research used a survey method by distributing questionnaires to 120 accounting students as a surrogate of future accountant. The results showed that the lower the silence and the cost of personal reporting, the more the accountant's intention to report fraud. Meanwhile, subjective norms have no effect on the accountant's intention to report fraud. The study also found that the perception of organizational support strengthened the influence of silence and subjective norms on whistleblowing intentions, but failed to moderate the relationship between personal reporting costs and whistleblowing. The results have implications for organizations and policymakers in designing a reporting system that can motivate accountants in reporting fraud.